Tertiary care centres must do more for patients with unknown conditions: Lessons learned from a child - Guido Filler; Lana Rothfels (The Beryl Institute, 2018)
Postural Orthostatic Tachycardia Syndrome (POTS) is a debilitating disease with a commonly non-uniform and unspecific presentation that makes diagnosis difficult. A twelve-year-old girl, recently diagnosed with Addison's Disease, was referred to paediatric nephrology for Fludrocortisone-induced nocturnal hypertension. She had fallen off the growth curve for both height and weight from the 50th percentile at birth to below the 5th percentile at presentation. The severity and multitude of her symptoms, including muscle weakness, poor body control, dizziness, light headedness, persistent fatigue, excessive sweating, tachycardia, chronic constipation and recurrent infection hinted at the unusual nature of this case of Addison's. At the time of referral, she had been seen by more than a dozen specialists and subspecialists as well as undergone a number of tests including neurophysiological testing without sufficient explanation. With the help of tilt-table testing, we established the diagnosis of POTS. There is a lack of tested treatment options for POTS, and we established dosing of pyridostigmine in children, based on the emerging literature in adults. While pyridostigmine therapy substantially improved her quality of life, it took another 6 years and referral outside the country, before a final unifying diagnosis was made. Eventually, the patient was diagnosed with Ehlers Danlos Syndrome with associated autonomic dysfunction, including POTS, as well as primary adrenal insufficiency. The parents and the patient experienced considerable stress due to the lack of willingness of many physicians that the family encountered to search for a diagnosis and a treatment.